RELEVANSI NILAI INFORMASI AKUNTANSI ALTERNATIF SERTA IMPLIKASINYA TERHADAP PROSES PENGAMBILAN KEPUTUSAN INVESTASI DENGAN MENGGUNAKAN SEQUENTIAL EXPLANATORY MIXED METHOD - Mada Purwanto Wahyu Nugroho; Ahmad Syifaudin (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2020)
Distortion of information is one of the inherent accounting risks in financial statements. Financial statements are one of the fundamental sources of information that can be used in investment decision making in the Indonesia stock exchange. If investors use this information, then investors also have the same risk that is the distortion of information contained in financial statements. This research tries to test whether stock prices can be more explained through alternative accounting information or information contained in financial statements. This research was conducted using a sequential explanatory mixed method. Using data on companies listed in the Business 27 index, tested using path analysis through multiple regression models, the results of this research indicate that alternative accounting information has not been able to explain variations in stock price changes compared to accounting information contained in financial statements. Meanwhile, the results of the analysis using qualitative data indicate there is a match between the results of quantitative analysis and qualitative analysis. Keywords: Value Relevance; Alternative Accounting Information; Investment Decisions